The Concealment of the State - Lindsey, Jason Royce (Contemporary Anarchist Studies, 2013)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Concealing the state frees us from admitting the unpleasant truth-in today's world we are utterly dependent upon the state's increasingly frantic efforts to control risk. To this end, states have created systems of coercion and surveillance that are difficult to reconcile with our theories of political legitimacy. The dominant ideology of contemporary politics has become the concealment of the state's overwhelming power and role in daily life. We prefer the comfortable illusion that we are autonomous individuals pursuing our plans in a free market. If we hold fast to that idea, then our distance from policy makers and dwindling political influence seems less important. Nonetheless, this book draws upon the anarchist tradition and a wide range of accessible policy examples (ranging from military organization and environmental regulations to scientific investment and education) to reveal the active role of contemporary states behind this ideological screen. Lindsey argues that we need a new politics that focuses on exposing and challenging the contemporary state's hidden agency. Otherwise, how can we democratically control the state when it denies, from the outset, having the ability to meet our demands?